2012
DOI: 10.5402/2012/134683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Treatment on Mechanical and Water-Sorption Properties Coconut Fiber-Unsaturated Polyester from Recycled PET

Abstract: Coconut fibers were used as reinforcement for unsaturated polyester resin from recycled PET that has been prepared using glycolysis and polyesterification reaction. Various concentrations of alkali, silane, and silane on alkalized fiber were applied and the optimum concentration of treatments was determined. Morphological and mechanical properties of the composite have also been investigated to study the effect of fiber surface treatment. The influence of water uptake on the sorption characteristics of composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…As the hydroxyl groups are reduced, the water resistance of WPCs become higher, similar findings were reported by Thaker et al 25 A similar result was also found by Munirah and Ahmad. 34 They claimed that the chemical treatment on composites possessed higher water resistance than untreated composites. Table 3 summarizes the percentage of water absorption in untreated and treated EPS/CSP WPCs.…”
Section: Resultsmentioning
confidence: 99%
“…As the hydroxyl groups are reduced, the water resistance of WPCs become higher, similar findings were reported by Thaker et al 25 A similar result was also found by Munirah and Ahmad. 34 They claimed that the chemical treatment on composites possessed higher water resistance than untreated composites. Table 3 summarizes the percentage of water absorption in untreated and treated EPS/CSP WPCs.…”
Section: Resultsmentioning
confidence: 99%
“…However, moisture absorption of natural fibres can be minimised by several processes such as coating [ 67 , 73 ], treatment with chemicals such as NaOH, acetylation, toluene diisocyanate, silane on alkali [ 64 , 74 77 ], use of coupling agents such as maleated anhydride grafted polypropylene (MAPP), maleic anhydride polyethylene (MAPE), silane [ 63 , 78 , 79 ]. A decrease in water absorption in coir fibres after surface treatments using NaOH, silane and alkalized silane was reported [ 73 ].…”
Section: Relatively Poor Tensile Strength Of Natural Fibres: a Major ...mentioning
confidence: 99%
“…Coupling agents improve the adhesion between fibre and matrix, thus aiding in reacting with the hydroxyl group and decrease in the rate of the diffusion process and hence reduction in moisture ingress [ 68 , 73 , 79 ]. Coatings such as latex coatings act in a similar way as coupling agents by partially shielding the pores on the surface of the fibre, thus reducing the penetration of moisture into the fibre.…”
Section: Relatively Poor Tensile Strength Of Natural Fibres: a Major ...mentioning
confidence: 99%
“…Currently, coating modification of the fiber surface is gradually becoming a hot research topic. The coating on the fiber surface can not only reduce the thermal stress between the fiber and the resin matrix during processing procedure and repair defects on the surface of fiber and damages caused by alkali treatment, but also improve the molecular structure of the fiber surface and improve the wettability of PET fiber in the resin matrix [9]. However, modification of PET fiber through surface coating has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%